Women's Power: Resilience and Resistance in Emily Dickinson's Poetry - Angga Pratama Armadi Putra; Zulfa Sakhiyya; Henrikus Joko Yulianto (Universitas Negeri Semarang, 2025)
Research on gender issues in literature has significantly developed in recent decades, reflecting the growing awareness among younger generations of past social injustices, particularly regarding gender representation. As Showalter (1989) argues, literature has long been a powerful medium for expressing critical perspectives on social norms across various genres, including poetry, novels, and drama. A notable literary figure in this context is Emily Dickinson, whose works subtly yet incisively critique patriarchal structures. The analysis focuses on how gender, power, and language are portrayed in Dickinson’s poetry. It examines her use of language as a tool to challenge social norms and deconstruct rigid gender identities. The research combines Critical Discourse Analysis (CDA), based on Fairclough’s model, with Feminist Critical Discourse Analysis. Judith Butler’s theory of gender performativity serves as the conceptual framework. Four of Dickinson’s poems were purposefully selected for analysis using textual and interpretative methods, supported by critical responses from postgraduate students. The findings reveal that Dickinson strategically utilizes metaphor, symbolism, and unconventional sentence structures as forms of resistance to gender norms. Her poems contain embedded critiques of patriarchal dominance and create space for reinterpreting gender identity beyond binary constraints. Literature provides a platform for marginalized voices to challenge deeply ingrained stereotypes and normalized ideologies, a fact affirmed by this study. Dickinson's poetic voice remains relevant in contemporary discussions. By integrating critical literacy and gender awareness into English language education, literature can effectively foster reflective perspectives on the power dynamics inherent in language and culture.